Nanoparticles Constructed from Neosartorya hiratsukae to Control Drechslera oryzae Causing Brown Spot of Rice - Kessara Unthuraloet; Kasem Soytong (Advances in biological sciences research/Advances in Biological Sciences Research, 2021)
The toxic chemical fungicides for plant disease control has been used by farmers for years. Those are faced hazardous effect to the surrounding environment, and the chemicals were toxic chemical residue remained in rice products which harmful to the consumers. It is increasing interested to search the new biological control agent to control the pathogen and to be promising as a biocontrol agent against the rice bast incidence in seriously infested rice fields. The aims of project was proved the fungus Neosartorya hiratsukae as a biological control agent to brown spot of rice (Oryza sativa) caused by Drechslera oryzae and developed a novel nanoparticles constructed from N. hiratsukae to control the rice brown spot. Result revealed that the aggressive isolate of D. oryzae was significantly inhibited by N. hiratsukae antagonistic fungus in bi-culture antagonistic evaluation. The growth of D. oryzae in bi-culture test was inhibited fungal colony and sporulation by 51 and 55 %, respectively. Bioassay of crude metabolite extract by methanol from N. hiratsukae gave the good inhibition of the colony growth and sporulation of D. oryzae which the ED50 of 1.7 and 92 ppm., respectively. The nanoparticles constructed from N. hiratsukae using electron spinning method found that nanoparticles SH-M expressed the best inhibition of the pathogen growth both colony and sporulation of the tested rice pathogen with the ED50 of 4 ppm. It is observed that nanoparticles SH-M had more effective control the pathogen than crude metabolite extract from N. hiratsukae. Pot experiment showed that nanoparticles SH-M actively expressed antifungal activity against brown spot of rice more than the inoculated control. It is interested that the rice plants treated with nanoparticles SH-M resulted to be better plant stands than the inoculated control. This is recorded for the first time using new antagonist, N. hiratsukae and its active compounds both in crude extracts and nanoparticles to control brown spot of rice.
Keywords: Mycotoxins in Agriculture and Food; Plant Pathogens and Fungal Diseases; Plant-Microbe Interactions and Immunity